Stochastic rainfall and catchment characteristics as an input to deterministic urban runoff models - Maksimovic,C; Vukmirovic,V (1992)
The paper deals with interaction of the stochastic features of storm and catchment characteristics and runoff. The following items in this process are stochastic: rainfall temporal and spatial characteristics; surface retention due to the seasonal variation of the surface cover (vegetation); infiltration due to the spatial variability of its parameters (conductivity and porosity) and of the antecedent moisture conditions. These items have been analyzed and the effect of the extreme statistics on the runoff are discussed. A hypothetical catchment is being used for the rainfall-runoff analysis. -from Authors